A rare primary lung tumor in children: Carcinoid tumor: Carcinoid tumor in children - Ülgen, Özge; Oksay, Sinem Can; Cağlar, Yasemin Mocan; Toksöz Yıldırım, Ayşe Nur; Girit, Saniye (Journal of Surgery and Medicine, 2025)
Bronchial carcinoids are rare childhood malignancies, comprising only a small proportion of pediatric lung tumors. This report details the case of a 9-year-old girl with persistent pneumonia that lasted one month and remained unresponsive to antibiotic therapy. Radiological imaging revealed atelectasis of the superior lobe of the left lung, while computed tomography showed an endobronchial lesion in the left main bronchus. An endobronchial biopsy confirmed the diagnosis of a typical bronchial carcinoid tumor. The tumor was completely resected using bronchoscopy, and cryotherapy was used to prevent the tumor’s recurrence. No evidence of tumor recurrence was observed in subsequent follow-up bronchoscopy. This case underscores the importance of considering bronchial carcinoid tumors in the differential diagnosis of pediatric patients with recurrent pneumonia or wheezing that is resistant to standard treatments. Through early identification and minimally invasive management, such as bronchoscopy and cryotherapy, it is possible to achieve successful outcomes and avoid more extensive surgery. Our findings add to the scarce literature on pediatric bronchial carcinoid tumors and highlight the instrumental role of prompt and accurate diagnosis in improving prognosis.